Multi-Omics Analysis Reveals a Regulatory Network of ZmCCT During Maize Resistance to Gibberella Stalk Rot at the Early Stage - Tang, Bozeng; Zhang, Zhaoheng; Zhao, Xinyu; Xu, Yang; Wang, Li; Chen, Xiao-Lin; Wang, Weixiang (Frontiers in Plant Science, 2022)
Gibberella stalk rot (GSR) caused by Fusarium graminearum is one of the most devastating diseases in maize, however, the regulatory mechanism of resistance to GSR remains largely unknown. We performed a comparative multi-omics analysis to reveal the maize early-stage resistance to GSR. We inoculated F. graminearum to the roots of susceptible (Y331) and resistant (Y331-∆TE) near-isogenic lines containing GSR-resistant gene ZmCCT for multi-omics analysis. Transcriptome detected a rapid reaction that confers resistant at 1~3 hpi as pattern-trigged immunity (PTI) response to GSR. Many key properties were involved in GSR resistance, including genes in photoperiod, and hormone pathways of salicylic acid and auxin. Activation of programmed cell death-related genes and a number of metabolic pathways at 6 hpi might be important to prevent further colonization. This is consistent with integrative analysis of transcriptomic and proteomics that resistant-mediated gene expression reprogramming exhibited a dynamic pattern from 3 hpi to 6 hpi. Further metabolomics analysis revealed that amount of many chemical compounds was altered in pathways associated with the phenylpropanoid biosynthesis and phenylalanine metabolism, that may play key roles to confer the GSR resistance. Taken together, we generated a valuable resource to interpret the defense mechanism during early GSR resistance.